2021
DOI: 10.1002/cncr.34057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of enfortumab vedotin in advanced urothelial cancer: Analysis from the Urothelial Cancer Network to Investigate Therapeutic Experiences (UNITE) study

Abstract: Background Enfortumab vedotin (EV) is a novel antibody‐drug conjugate approved for advanced urothelial cancer (aUC) refractory to prior therapy. In the Urothelial Cancer Network to Investigate Therapeutic Experiences (UNITE) study, the authors looked at the experience with EV in patient subsets of interest for which activity had not been well defined in clinical trials. Methods UNITE was a retrospective study of patients with aUC treated with recently approved agents. This initial analysis focused on patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 24 publications
10
34
0
Order By: Relevance
“…This intriguing observation in a treatment setting where predictive biomarker data have been lacking, deserves further validation in independent patient cohorts. Despite the relatively smaller sample size of this cohort, the observed response rate of 41%, as well as mPFS of 5.1 months, and mOS of 10.2 months are consistent with data previously reported by larger clinical trials and retrospective studies in this patient population ( 9 , 12 , 26 ). Consequently, this data, while hypothesis-generating, sheds important light on the biomarker landscape in aUC, where treatment decisions must frequently be made in the refractory setting among the several therapeutic options available.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This intriguing observation in a treatment setting where predictive biomarker data have been lacking, deserves further validation in independent patient cohorts. Despite the relatively smaller sample size of this cohort, the observed response rate of 41%, as well as mPFS of 5.1 months, and mOS of 10.2 months are consistent with data previously reported by larger clinical trials and retrospective studies in this patient population ( 9 , 12 , 26 ). Consequently, this data, while hypothesis-generating, sheds important light on the biomarker landscape in aUC, where treatment decisions must frequently be made in the refractory setting among the several therapeutic options available.…”
Section: Discussionsupporting
confidence: 91%
“…Previous analyses have found low albumin levels predict inferior outcomes to ICI in patients with mUC and better ECOG performance scores (<2) predict improved outcomes to ICI in patients with aUC ( 38 , 44 ). Another analysis of EV outcomes in a multicenter cohort UNITE study reported consistent responses to EV in patients with both ECOG PS < 2 and ≥ 2 respectively ( 26 ). The same UNITE study dataset noted numerically higher responses to EV in patients with a pure urothelial histology as compared to patients with a variant histology component (58% vs 42%, p=0.06).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Erdafitinib is an alternative for platinum-refractory mUC with selected fibroblast growth factor receptor ( FGFR ) alterations ( FGFR2 mutations or FGFR3 mutations/fusions) [ 7 ]. The antibody–drug conjugate enfortumab vedotin, targeting nectin-4, is currently the preferred option for patients with ChT and ICI-refractory disease [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%